Efeito de diferentes espaçamentos e densidades de semeadura sobre o desenvolvimento do feijoeiro (Phaseolus vulgaris L.) - Arf, Orivaldo; Eustáquio de Sá, Marco [UNESP]; Satoru Okita, Carlos; Akira Tiba, Marcos; Guerreiro Neto, Gerônimo; Yukio Ogassawara, Fábio [UNESP] (My University, 1996)
This work was carried out in Selvíria, MS, Brazil, under irrigation, in May, 1991, in an attempt to verify the influence of different row spacing (.20 x .80; .30 x .80; .20 x .70; .30 x .70; .60 and .50 m) and plant densities in the row (8, 12, and 16 plants/m) on the behavior of beans, cultivar Ouro. Evaluations were performed during the essay as follows: weight of plant dry matter, production components, yields, seed germination, and seed classification according to size. The results show a reduction in the production of plant dry matter and in the number of pods and seeds per plant. As the number of plants was increased, however, yielding increased and was the highest value found in the 16 plants/m density. Spacing did not affect crop yielding. The germination of harvested seeds and their percentage per sieve were not affected by the spacing and densities used.

Em maio de 1991, foi instalado um experimento, sob irrigação, no município de Selvíria, MS, com o objetivo de verificar a influência de diferentes espaçamentos entre linhas (0,20 x 0,80; 0,30 x 0,80; 0,20 x 0,70; 0,30 x 0,70; 0,60 e 0,50 m) e densidades de semeadura (8, 12 e 16 plantas/m), incluindo a utilização de linha dupla, sobre o comportamento do feijoeiro cultivar Ouro. Foram avaliados: o peso da matéria seca das plantas, os componentes de rendimento, a produtividade, a germinação das sementes e a sua classificação por tamanho. O aumento do número de plantas na linha ocasionou redução na produção de matéria seca das plantas, e no número de vagens e de sementes por planta; porém a produtividade foi aumentada, sendo o maior valor encontrado na densidade de 16 plantas/m. Já os espaçamentos; não influenciaram na produtividade da cultura. A germinação das sementes colhidas e sua percentagem por peneira não foram influenciadas pelos espaçamentos e pelas densidades utilizadas.
Effect of different spacing and densities of sowing on the development of beans (Phaseolus vulgaris L.)
Keywords: Double row; Germination; Seeds; Sprinkling system